(3QSGdI aj GdeaQhVGJs ((3OeTb s)
(3ChdgG (B:s
(3HYO GdHSedI dfaQV KdGKI GeOGO SHHI fSHI GdGUaQ Edj GdGhSW cfSHI Gdj GdGYXe s
(3BNQgG (B:s
(3hJbSeI Ydi GdeYdhe jNQL GdeYdhe hJVQH GdeYdhe aj GdeYdhe hJbSeI Ydj GdeYdhe ajNQL s
(3Vef eLehY , JQJjHgG (B: 5s
(3HgG fXGe GdJYbjHIs
(3cJH jBNQgG WGdY gPg GdQSGdI GdgfOSjI eMeO Hf LhHGf GdeQGZj aj GdeOQSI GdfXGejIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdQjGVjGJs